2016
DOI: 10.1002/jcc.24467
|View full text |Cite
|
Sign up to set email alerts
|

Calculating protein–ligand binding affinities with MMPBSA: Method and error analysis

Abstract: MMPBSA methods have become widely adopted in estimating protein-ligand binding affinities due to their efficiency and high correlation with experiment. Here we investigated different computational alternatives on their impact to the agreement of MMPBSA calculations with experiment. Seven receptor families with both high-quality crystal structures and binding affinities were selected. We first studied the performance of nonpolar solvation models and found that the modern approach that separately models hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
196
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(205 citation statements)
references
References 146 publications
(207 reference statements)
7
196
2
Order By: Relevance
“…Our previous studies have shown that a high protein dielectric constant best reproduces experimental results in MMPBSA calculations when charged ligands/active sites present in globular proteins 118, 124 . A similar conclusion can also be drawn in the tested membrane protein: when the “default” protein dielectric value of 4 is used, the correlation is reduced from 0.79 to 0.75 with INP=1.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Our previous studies have shown that a high protein dielectric constant best reproduces experimental results in MMPBSA calculations when charged ligands/active sites present in globular proteins 118, 124 . A similar conclusion can also be drawn in the tested membrane protein: when the “default” protein dielectric value of 4 is used, the correlation is reduced from 0.79 to 0.75 with INP=1.…”
Section: Resultsmentioning
confidence: 78%
“…The membrane dielectric constant was set to be 7.0 124 . And the protein dielectric constant was set to be 20.0 due to the presence of charged ligand molecules 118, 124 . The water phase ionic strength was set to be 150 mM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This classical surface area-dependent method is widely adopted for practical biomolecular applications to estimate the total nonpolar solvation contribution in the case of macromolecules, although its deficiencies were also reported due to overlooking solvation contributions of interior (buried) atoms. 24, 3352 Newer models were proposed to overcome these deficiencies, though they are yet to be widely received by the community.…”
Section: Introductionmentioning
confidence: 99%